Quranic Leadership: The Effort to Realize the Integrity of Leaders in Preventing Corruption - Chanifah, Nur; Samsudin, Abu; Hajar Ansori, Ibnu (International Journal of Educational Management and Innovation, 2024)
This Study aims to analyse how the Quran explains the integrity of leaders as an effort to prevent corruption in Indonesia. This is urgent, because the problem of corruption cannot only be solved by building a legal and judicial system, but also requires prevention efforts through character building, especially related to leaders. It is categorized qualitative research with literature review by conceptual approach. The research analysis uses descriptive-qualitative analysis with the stages, namely editing, classifying, and conclusion. The results showed that the Quranic Leadership to prevent corruption in Islam is reflected in the character or personality of the Prophet Muhammad, namely shidiq (honest), amanah, fathanah (intelligent), and tabligh (communicative and transparent). If it is associated with leadership characteristics described by all classical and modern management experts such as the theories of Warren Bennis and James O'Tool, then these characteristics have been reflected by the Prophet Muhammad throughout his life. Even the Prophet had first applied it through the instructions of Allah SWT contained in the holy book, Qur’an.